Modular photo-induced RAFT polymerised hydrogels via thiol–ene click chemistry for 3D cell culturing. Issue 39 (21st September 2017) - Tan, Vincent T. G.; Nguyen, Duyen H. T.; Utama, Robert H.; Kahram, Mohaddeseh; Ercole, Francesca; Quinn, John F.; Whittaker, Michael R.; Davis, Thomas P.; Justin Gooding, J.
Abstract : Visible-light induced thiol–ene click gelation of RAFT polymers, creating a modular hydrogel system for 3D cell culture assays. Abstract : Cell behaviour changes as a result of the local environment, particularly when transitioning from two dimensional (2D) to three dimensional (3D) environments. It has been acknowledged that there is a need for efficient, tuneable and reproducible methods for making 3D cell cultures to further understand cell behaviour in 3D environments. The development of extracellular matrix (ECM) mimics has gained popularity as a way to create highly tuneable materials that resemble the native environment around cells. The modular nature of synthetic hydrogels means that they have the potential as ECM mimics for 3D cell cultures with tuneable mechanical and chemical properties. Herein, reversible addition fragmentation chain transfer (RAFT) polymerisation was used to synthesise poly(ethylene glycol)methyl ether acrylate (PEGMEA). Hydrogels with tuneable mechanical and cell adhesive properties were synthesised. Norbornene was used as a functional unit for both crosslinking and addition of biomolecules via thiol–ene click chemistry. To obviate the need for UV light for cross-linking of the hydrogel, visible light stimulated eosin-Y was used to induce the thiol–ene reaction. Pancreatic cancer cells (Kras G12D and p53 R172H ) were seeded on the hydrogels to confirm that the cytotoxicity of the hydrogels was low. The attachment of CRGDS onto the hydrogel was demonstrated as a means to improve cell adhesion.